Navigators of the contemporary : why ethnography matters - Westbrook, David A. (University of Chicago Press, 2008)
As the image of anthropologists exploring exotic locales and filling in blanks on the map has faded, the idea that cultural anthropology has much to say about the contemporary world has likewise diminished. In an increasingly smaller world, how can anthropology help us to tackle the concerns of a global society? David A. Westbrook argues that the traditional tool of the cultural anthropologist--ethnography--can still function as an intellectually exciting way to understand our interconnected, yet mysterious worlds. Navigators of the Contemporary describes the changing nature of ethnography as an.